2012
DOI: 10.1089/zeb.2012.0746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrite on Development of Embryos and Early Larval Stages of the Zebrafish (Danio rerio)

Abstract: Epidemiological studies suggest that high nitrate levels in food and water may cause birth defects or spontaneous abortions in humans. Experimental mammalian studies show that high nitrite levels adversely affect reproductive outcomes, but have not shown congenital malformations. Consequently, the teratogenic potential of nitrite is unclear. In this study, the effects of nitrite on development of zebrafish embryos and early larval stages were investigated. Eggs were exposed to ethanol (a known teratogen), nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
4
25
0
Order By: Relevance
“…According to other studies in zebrafish, developmental defects, growth suppression and high mortality occur at much higher concentrations (100-300 mg/L) [6,7]. Although few studies indicated that nitrate and nitrite exposure exerts adverse effect on nervous system [8,31], to our knowledge so far this is the first study to reveal the specific effect of nitrate and nitrite on the activity of DA neurons.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…According to other studies in zebrafish, developmental defects, growth suppression and high mortality occur at much higher concentrations (100-300 mg/L) [6,7]. Although few studies indicated that nitrate and nitrite exposure exerts adverse effect on nervous system [8,31], to our knowledge so far this is the first study to reveal the specific effect of nitrate and nitrite on the activity of DA neurons.…”
Section: Discussionmentioning
confidence: 67%
“…Both acute and chronic exposures of nitrate and nitrite increase mortality and impair growth and reproduction [4,5]. Some studies in zebrafish at different life stages also reported toxic effects such as developmental defects, high mortality, and growth suppression [6,7]. Though some studies have shown the maternal exposure to high nitrate concentrations in drinking water and food may increase the risk of neuronal defects in infant [8], the information of specific mechanisms in the nervous system affected by nitrate and nitrite exposure is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Though the toxicological mechanisms and health risks of nitrite have been widely investigated [1], [10], little is known whether high level of nitrite is toxic to vertebrate early heart development and performance.…”
Section: Introductionmentioning
confidence: 99%
“…; Simmons et al. ), we took care not to take fish from aquaria where high nitrite levels (>0.1 mg/l) were measured within three days prior to the experiments. Focal individuals and most of the stimulus fish were used only once to avoid effects of multiple testing.…”
Section: Methodsmentioning
confidence: 99%
“…To minimize potential biases due to differences in intrinsic state (van Havre & FitzGerald 1988;Frommen et al 2012), we only used fish showing no signs of developing breeding coloration or egg production. As high nitrite levels are known to affect development, outer appearance and swimming behavior of fish (Wang et al 2006;Rodrigues et al 2007;Simmons et al 2012), we took care not to take fish from aquaria where high nitrite levels (>0.1 mg/l) were measured within three days prior to the experiments. Focal individuals and most of the stimulus fish were used only once to avoid effects of multiple testing.…”
Section: Experimental Subjectsmentioning
confidence: 99%